Genetic and genomic resources to study natural variation in Brassica rapa. (22nd December 2020) - Lou, Ping; Woody, Scott; Greenham, Kathleen; VanBuren, Robert; Colle, Marivi; Edger, Patrick P.; Sartor, Ryan; Zheng, Yakun; Levendoski, Nathan; Lim, Jan; So, Calvin; Stoveken, Brian; et al.
Abstract: The globally important crop Brassica rapa, a close relative of Arabidopsis, is an excellent system for modeling our current knowledge of plant growth on a morphologically diverse crop. The long history of B. rapa domestication across Asia and Europe provides a unique collection of locally adapted varieties that span large climatic regions with various abiotic and biotic stress‐tolerance traits. This diverse gene pool provides a rich source of targets with the potential for manipulation toward the enhancement of productivity of crops both within and outside the Brassicaceae. To expand the genetic resources available to study natural variation in B. rapa, we constructed an Advanced Intercross Recombinant Inbred Line (AI‐RIL) population using B. rapa subsp. trilocularis (Yellow Sarson) R500 and the B. rapa subsp. parachinensis (Cai Xin) variety L58. Our current understanding of genomic structure variation across crops suggests that a single reference genome is insufficient for capturing the genetic diversity within a species. To complement this AI‐RIL population and current and future B. rapa genomic resources, we generated a de novo genome assembly of the B. rapa subsp. trilocularis (Yellow Sarson) variety R500, the maternal parent of the AI‐RIL population. The genetic map for the R500 x L58 population generated using this de novo genome was used to map Quantitative Trait Loci (QTL) for seed coat color and revealed the improved mapping resolution afforded by this new assembly.